Continuous Negative Abdominal Pressure Reduces Ventilator-induced Lung Injury in a Porcine Model. (July 2018) - Yoshida, Takeshi; Engelberts, Doreen; Otulakowski, Gail; Katira, Bhushan; Post, Martin; Ferguson, Niall D.; Brochard, Laurent; Amato, Marcelo B. P.; Kavanagh, Brian P.
Abstract : Background: In supine patients with acute respiratory distress syndrome, the lung typically partitions into regions of dorsal atelectasis and ventral aeration ("baby lung"). Positive airway pressure is often used to recruit atelectasis, but often overinflates ventral (already aerated) regions. A novel approach to selective recruitment of dorsal atelectasis is by "continuous negative abdominal pressure." Methods: A randomized laboratory study was performed in anesthetized pigs. Lung injury was induced by surfactant lavage followed by 1 h of injurious mechanical ventilation. Randomization (five pigs in each group) was to positive end-expiratory pressure (PEEP) alone or PEEP with continuous negative abdominal pressure (−5 cm H2 O via a plexiglass chamber enclosing hindlimbs, pelvis, and abdomen), followed by 4 h of injurious ventilation (high tidal volume, 20 ml/kg; low expiratory transpulmonary pressure, −3 cm H2 O). The level of PEEP at the start was ≈7 ( vs . ≈3) cm H2 O in the PEEP ( vs . PEEP plus continuous negative abdominal pressure) groups. Esophageal pressure, hemodynamics, and electrical impedance tomography were recorded, and injury determined by lung wet/dry weight ratio and interleukin-6 expression. Results: All animals survived, but cardiac output was decreased in the PEEP group. Addition of continuous negative abdominal pressure to PEEP resulted in greater oxygenation (PaO2 /fractional inspired oxygen 316 ± 134 vs . 80 ± 24 mmHg at 4 h, P = 0.005), compliance (14.2 ± 3.0 vs . 10.3 ± 2.2 ml/cm H2 O, P = 0.049), and homogeneity of ventilation, with less pulmonary edema (≈10% less) and interleukin-6 expression (≈30% less). Conclusions: Continuous negative abdominal pressure added to PEEP reduces ventilator-induced lung injury in a pig model compared with PEEP alone, despite targeting identical expiratory transpulmonary pressure. Abstract : In a pig adult respiratory distress syndrome model, addition of continuous negative abdominal pressure (−5 cm H2 O) to positive end-expiratory pressure (PEEP), compared with PEEP alone (where transpulmonary pressure was matched in each group), resulted in better oxygenation, compliance, and homogeneity of ventilation, as well as less lung injury. PEEP with continuous negative abdominal pressure might be a treatment option for adult respiratory distress syndrome by recruiting atelectasis and minimizing ventilator-induced lung injury, but its efficacy and long-term effects in patients are not yet known.Supplemental Digital Content is available in the text.